Non-criteria Antiphospholipid Antibodies: a narrative review - Funke,Andreas (2020)
SUMMARY The 2006 Revised Sapporo Classification Criteria for Definite Antiphospholipid Syndrome included as laboratory criteria the tests for antiphospholipid antibodies whose accuracy was regarded as satisfactory according to the evidence available at that time. In practice, however, the sensitivity and specificity of these “criteria” of antiphospholipid antibodies are sometimes insufficient for identifying or ruling out antiphospholipid syndrome. It has been studied whether the accuracy of the laboratory diagnosis of the syndrome could be improved by testing for non-criteria antiphospholipid antibodies. In this work, we review evidence on the clinical associations and diagnostic value of the most commonly studied non-criteria antibodies, namely: antiphosphatidylethanolamine, anti-annexin A5, anti-prothrombin, anti-phosphatidylserine/prothrombin complex, IgA anticardiolipin, and IgG anti-domain I of the β2 glycoprotein antibodies.